Combining ability of six s7 generation of corn hybrid parents from half dialel crossesof Maize in a Half Diallel Crosses - Dwitama, Niko; Rustikawati, Rustikawati; Suryati, Dotti; Herison, Catur (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2018)
Combining ability is the genotype's ability to pass on the desired character to the offspring. Combining ability information is needed to determine the crossed pairs in the formation of hybrid varieties. The purpose of this study was to obtain information on the combining ability value of six S7 generation of inbreed maize. The experiment was conducted in September 2015 until January 2016, at Medan Baru Experimental Station of Faculty of Agriculture, at Kandang Limun village, Muara Bangkahulu Sub-district, Bengkulu City. The experiment was prepared in a Randomized Block Design (RCBD) with 15 corn hybrid treatments including: G1XG3, G1XG6, G3XG6, G1XG7, G3XG7, G6XG7, G1XG8, G3XG8, G6XG8, G7XG8, G1XG9, G3XG9, G6XG9, G7XG9 and G8xG9. Each experimental unit was repeated three times obtaining 45 experimental plots. Estimation of general combining ability (GCA) value and specific combining ability (SCA) of each inbreed strain were conducted with Griffing model IV method. The results showed that genotype G1 and G3 had positive GCA values for all characters except plant height. The G7XG1 cross combination showed a positive SCA on all characters even higher in plant height and stem diameter. The G8XG6 cross combination showed high SCA values for leaf number characters, weight of husk-less cob, number of seeds per seed-line, weight of grain per ear, and grain yield per plot.Keywords: Hybrid, corn, GCA and SCA